Analysis On Financial Performance Of Takaful Operators In Malaysia Through Claim Ratio, Risk-Based Capital And Intellectual Capital - Nur Amalina Syafiqa Binti Kamaruddin
The insurance industry plays an important role in the world, especially in well-developed countries. This industry is considered crucial because it functions to protect people and business operations from any risks. Takaful, which has been growing in popularity in the insurance sector, must maintain good market growth. Thus, this study aims to assess the financial performance of takaful operators through claim ratio, risk-based capital (RBC), and intellectual capital towards two profitability ratios, which are return on asset (ROA) and return on equity (ROE). This study was conducted using a panel data set of 15 listed takaful operators in Malaysia over the period 2015-2019; meanwhile, the secondary data was taken from the operators’ audited financial statements. The results were obtained by computing the claim ratio, the minimum capital level required in RBC, the value-added intellectual capital (VAIC) score, and percentages of ROA and ROE level of each takaful operator. A panel data regression model and Pearson correlation were used to determine the effects as well as the relationships that claim ratio, RBC, and VAIC have towards the profitability of takaful operators. The result of the claim ratio showed that family takaful fund has a higher claim ratio, which indicated low profit compared to general takaful fund. The RBC result also supported general takaful better than most family takaful by fulfilling the supervisory target capital level of 130% as required by Bank Negara Malaysia (BNM). As for the VAIC score, most of the takaful operators showed positive VAIC scores, which implies they are able to fully utilize the companies’ resources that lead to an outstanding management leader stewardship. Both average levels of ROA and ROE showed positive results, indicating most family and general takaful operators are able to efficiently generate good profits using their resources’ level. The implications of this study can help the public obtain a clearer picture of the Malaysian takaful market and further assist the takaful operators towards better improvement in assessing their future performance by applying the intellectual capital method.